Peningkatan Kemampuan Guru dalam Membuat Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi (TIK) Melalui In House Training - Harmana, Harmana (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
Learning media is one of the supporting factors in the success of the teaching and learning process. This research started from the problem that there are 75% of teachers who are not proficient in making and using learning media based on information and communication technology. The purpose of this study is to improve the ability of teachers in making information technology-based learning media through IHT. This type of research is school action research. The research subjects were 12 teachers at SD Negeri Rowosari 01 Semarang City. Data collection techniques used interviews, observations, questionnaires, and documentation studies. The data analysis technique in this research is comparative descriptive. This study describes whether IHT activities with an andragogy approach can improve teacher skills in making ICT-based learning media. The results of the pre-test were compared with the results of the post-test and product scores to see an increase in the teacher's ability. Data validation uses technical triangulation and source triangulation. The results of this study indicate that: 1) The implementation of in-house training with an andragogy approach has succeeded in increasing the ability of teachers to create learning media. The mean baseline score increased from 60.8 to 85.4. Indicators of success can be met with the results of 11 teachers who achieved a completeness score of 76. 2) IHT steps that can improve teacher abilities are needs analysis with the Principal and participants, formulation of goals and objectives, program development, preparation of action plans, program implementation preceded with participant decision making, observation, and reflection.